Languge Hybrid; Code Switching and Code Mixing by Students of Islamic Secondary School in Banyuwangi - Ulfa Gusnaini; Rina Mahdiyana; Devinia Hepdian Syafitri (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2020)
Code-switching and Code-mixing are commonly treated as a phenomenon of the spoken language, and in linguistics referring to using more than one language in conversation. This research is done in Al-Kautsar Modern Female Islamic Boarding School (PPMP Al-Kautsar) Srono, Banyuwangi with the participant are all of Al-Kautsar students. This research using the observation method. The steps for analysis are first, the researchers collected notes and transcripts. Second, each data are labeled. Third, all codes identified so that the results are obtained. The entire code mix/switching founded are included as interstitial code mix/switching. There are several factors in using Code-switching and Code-mixing. The first is because of the habit of adding certain phrases such as what is? as the replacement of certain words or phrases. The second is the lack phase of finding the right words from Indonesian, Javanese, or Arabic into English considering the conversation is expected to keep running. From the observation, it is known that the phenomena of code mix/switching are occurred to smooth the communication function.